ANALISIS KANDUNGAN MINYAK DANSTRUKTUR KOMUNITAS DIATOM DAN MAKROZOOBENTHOS DI PERAIRAN KOLONG LAUT KARIMUN PROVINSI KEPULAUAN RIAU (Jurnal Kajian Lingkungan, 2013)
This research was conducted on April 2013 in the Kolong Laut Waters, Karimun District, Karimun Regency, Riau Archipelago Province. It aims to analyze of oil content in water and sediment and the structure community of diatom and macrozoobenthos. Method used was a survey method with five stasions each were selected for the sampling. Sample were analyzed in the Aquatic Ecology Laboratory and Food Chemistry Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The results showed that the mean oil content in water varies from 0.0003to0.0021 ppm andin sediment varies from 26 to 232 ppm. According to standard quality value of sea water, oil content of water has not exceeded the threshold value (<5 ppm) and oil content of sediment has exceeded the threshold value (>100 ppm). The diatom abundance ranged from 317 â 600cel/l consisted of 11 genus with Diversity index (Hâ) 1,7141 â 2,0975; Uniformity Index (E) 0,8467 â 0,9717and Dominance Index (C) 0,2654 â 0,3361. While the macrozoobenthos abundance ranged from 607 â 2489 Ind/m2 consisted of 11 genus with Diversity index (Hâ) 1.7141 â 2.2424; Uniformity Index (E) 0.8467 â 0.9717 and Dominance Index (C) 0.2433 â 0.3361. Simple linier regression analyses between oil content in water with diatom abundance indicates negative correlation (Y = 554 - 27760x, R2 = 0,021and r = 0,145) and between oil content in sediment with makcrozoobenthos abundance as well as (Y = 1546 â 0.486x, R2 = 0.001 and r = 0.032).Key words: Oil, diatom, macrozoobenthos, Kolong Laut Karimun